1981
DOI: 10.2165/00003088-198106050-00005
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of Antipyrine and Phenytoin Correlated with Age and Liver Volume in Man

Abstract: The half-life and metabolic clearance rate (MCR) of antipyrine and phenytoin were determined in 14 young (mean age: 28.8 +/- 8.3 (SD) years] and in 14 elderly [mean age: 83.5 +/- 7.1 (SD) years] subjects and correlated with liver volume, which was determined by ultrasonic scanning, to see if an age-dependent difference in drug metabolism could be explained by a reduced liver weight with age. The size of the liver was smaller in the elderly subjects even when related to decreased body surface. A significant dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(38 citation statements)
references
References 29 publications
2
35
0
1
Order By: Relevance
“…However, the change in the volume of distribution and slightly higher clearance may reflect alterations in protein binding. It has been shown that plasma concentrations of albumin decrease with age (Woodford-Williams et al, 1964) leading to changes in free drug fraction and consequently to changes in clearance and volume of distribution (Greenblatt et al, 1980 (Triggs & Nation, 1975;Hayes et al, 1975;Bach et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…However, the change in the volume of distribution and slightly higher clearance may reflect alterations in protein binding. It has been shown that plasma concentrations of albumin decrease with age (Woodford-Williams et al, 1964) leading to changes in free drug fraction and consequently to changes in clearance and volume of distribution (Greenblatt et al, 1980 (Triggs & Nation, 1975;Hayes et al, 1975;Bach et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to elderly individuals (older than 65 years, who have a decreased capacity to metabolize phenytoin because of age-related losses in liver functionality), [24][25] pregnant women taking phenytoin have increased dosage requirements, particularly during the third trimester. [26][27][28][29] The main reason for this change is that, although both have decreased protein binding due to low albumin concentrations (hypoalbuminemia) and consequently increased unbound fraction in plasma, pregnant women usually show increased metabolism of phenytoin (apart from a decreased bioavailability due to malabsorption).…”
Section: Bringing Theory To the Clinical Setting: Application To A Rementioning
confidence: 99%
“…In a manner similar to the kidney, the liver undergoes a number of changes with age that includes a reduction in blood flow (31) and mass (or volume) (32,33). Reduced blood flow might suggest a reduction in the clearance of those compounds with a high hepatic clearance (or high extraction ratio, nonrestrictively cleared).…”
Section: Hepatic Metabolismmentioning
confidence: 99%
“…It is more difficult to interpret the changes in liver mass. Several studies have shown a direct correlation between liver mass and clearance of compounds with a low clearance and that undergo oxidative metabolism (antipyrine and phenytoin) (33,34 Figure 6. Antipyrine clearance as a function of age in 307 healthy male subjects reason for this is the fact that half-life is a parameter dependent on clearance and volume of distribution.…”
Section: Hepatic Metabolismmentioning
confidence: 99%